The money problem : rethinking financial regulation - Ricks, Morgan (The University of Chicago Press, 2016)
Years have passed since the world experienced one of the worst financial crises in history, and while countless experts have analyzed it, many central questions remain unanswered. Should money creation be considered a 'public' or 'private' activity - or both? What do we mean by, and want from, financial stability? What role should regulation play? How would we design our monetary institutions if we could start from scratch? In 'The Money Problem', Morgan Ricks addresses all of these questions and more, offering a practical yet elegant blueprint for a modernized system of money and banking.